Strong Split Independent Domination in Fuzzy Graphs - P. Gladyis; C. V. R. Harinarayanan; R. Muthuraj (International Journal of Mathematics And its Applications, 2016)
An independent dominating set D of a fuzzy graph G=(σ, μ) is a split dominating set if the induced subgraph H=(V-D, σ', μ') is disconnected. The minimum of the fuzzy cardinalities of a split independent dominating sets of G is called the split independent domination number γ_sif(G) of G. An independent dominating set D of a fuzzy graph G=(σ, μ) is a strong split independent dominating set if the induced subgraph H=(V-D, σ', μ') is totally disconnected. The minimum of the fuzzy cardinalities of a strong split independent dominating sets of G is called the strong split independent domination number γ_ssif(G) of G. In this paper we study a strong split independent dominating sets of fuzzy graphs and investigate the relationship of γ_ssif(G) or γ_ssif with other known parameter of G.